Persepsi Remaja Berhijab Terhadap Penggunaan Hijab dalam Iklan Safi Hair Fall Treatment Shampoo - Aniza, Tiara Alifia; Assyfa, Melvia; Azzahra, Nabilla (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
The current shift in marketing targeting from demographic considerations to consumer psychography includes expectations, needs, fears, beliefs, opinions, and attitudes that can shape choices and determine the choices that consumers will choose. Therefore, marketing needs to be personalized so that every consumer problem can be met by marketers. In Indonesia there are various brands of shampoos that consumers can choose from, such as Safi as a case of this research because the ads take different marketing ways in addition to touching religious values. To market her products, Safi took out an advertisement for a hair loss treatment shampoo product featuring a hijab withdrawal scene in lieu of hair on her shampoo ad model. This has never been found in advertising other shampoo products, especially in Indonesia. This article aims to find out more about the perception of the audience, namely teenagers, especially hijab students against the advertisement of Safi Hair Fall Treatment Shampoo. This research uses a descriptive qualitative approach. The results of this research obtained so that the results can later be used as an advertising evaluation material for advertiser companies and advertising agencies both involved practically or not.